Novel Emergency Department Risk Score Discriminates Acute Coronary Syndrome Among Chest Pain Patients With Known Coronary Artery Disease. Issue 4 (December 2016) - Crim, Matthew T.; Berkowitz, Scott A.; Saheed, Mustapha; Miller, Jason; Deutschendorf, Amy; Gerstenblith, Gary; Hill, Peter; Korley, Frederick K.
Abstract : Background: Patients with known coronary artery disease presenting to the emergency department (ED) with chest pain are often admitted, yet may not be having an acute coronary syndrome (ACS). Methods: We assessed whether the use of a novel risk score and a modified thrombolysis in myocardial infarction risk score obtained in the ED could discriminate which of these high-risk patients have ACS. Chart review was performed on a cohort of 285 patients with known coronary artery disease presenting to the ED with chest pain thought to be of ischemic origin and admitted to the hospital. The ED variables were assessed with logistic regression for their association with eventual ACS diagnosis at hospital discharge. ACS was diagnosed in 74 (26%) of the patients. Results: Non-ACS patients had a 2-day median length of stay and 6875 median inpatient (post ED) hospital charges (not including physician fees), totaling 566 hospital bed days and 1, 871, 250 for the 211 (74%) non-ACS patients. A novel risk score, including (1) history of prior revascularization, (2) comorbid chronic kidney disease, (3) onset of chest discomfort at rest, (4) dynamic electrocardiogram changes in the ED, (5) elevated troponin I (>0.05 ng/mL) in the ED, and (6) associated illness at presentation, discriminated ACS and non-ACS with a c statistic of 0.767; the c statistic for a modified thrombolysis in myocardial infarction risk score was 0.712. Conclusions: Application of these risk scores may reduce the number of potentially avoidable admissions and their associated hazards and costs.